Validation and Characterization of a Seed Number Per Silique Quantitative Trait Locus qSN.A7 in Rapeseed (Brassica napus L.) - Zhu, Yaoyao; Ye, Jiang; Zhan, Jiepeng; Zheng, Xiaoxiao; Zhang, Jiangjiang; Shi, Jiaqin; Wang, Xinfa; Liu, Guihua; Wang, Hanzhong (Frontiers in Plant Science, 2020)
Seed number is a key character/trait tightly related to the plant fitness/evolution. and crop domestication/improvement. The seed number per silique (SNPS) shows a huge variation from several to more than 30, however the underlying regulatory mechanisms are poorly known, which has hindered its improvement. To answer this question, several representative lines with extreme SNPS were previously subjected to systematic genetic and cytological analyses. The results showed that the natural variation of seed number per silique is mainly controlled by maternal and embryonic genotype, which are co-determined by ovule number per ovary, fertile ovule ratio, ovule fertilization rate and fertilized ovule development rate. More importantly, we also mapped two repeatable QTLs for SNPS using the F2:3 population derived from Zhongshuang11 and No.73290, of which the major QTL qSN.A6 has been fine-mapped. In the current study, the near-isogenic lines (NILs) of qSN.A7 were successfully developed by the successive backcross of F1 with Zhongshuang11. First, the effect of qSN.A7 was validated by evaluating the SNPS of two types of homozygous NILs from BC3F2 population, which showed a significant difference of 2.23 on average. Then, qSN.A7 was successfully fine-mapped from the original 4.237 to 1.389 Mb, using a BC4F2 segregating population of 2551 individuals. To further clarify the regulatory mechanism of qSN.A7, the two types of homologous NILs were subjected to genetic and cytological analyses. The results showed that the difference in SNPS between the two homologous NILs was determined by the embryonic genotypic effect. Highly accordant with this, no significant difference was observed in ovule number per ovary, ovule fertility, fertilization rate and pollen fertility between the two homologous NILs. Therefore, the regulatory mechanism of qSN.A7 is completely different from the cloned qSS.C9 and qSN.A6. These results will advance the understanding of SNPS and facilitate gene cloning and molecular breeding in Brassica napus.